Bedsore is a curse in disguise: capturing the zeitgeist - Yadav, Anand; Kaushal, Rituja (International Surgery Journal, 2020)
Background: Development of a bedsore is always avoidable still its worldwide prevalence fluctuates between 0%-56%. Bedsores are maximally observed in patients who are on long term care, in intensive care, immuno-compromised or on home care. Methods: In a tertiary care center-JK hospital, Bhopal, a longitudinal observational study was done for a duration of 3 years, on all registered in-patients, to understand the trend of bedsore rates on monthly basis. Results: In our study, even though, on yearly basis, average of rates is showing a declining trend in favorable manner yet higher statistical analysis (ANOVA test p value = 0.054) has decrypted the non-significant results. Conclusions: Timely and appropriate prophylactic interventions are needed to overcome the increased bedsore rates. Checklist based surveillance and monitoring should be a pressing priority. Cochrane reviews are also suggestive of incorporation of organizational changes, risk assessment tools, wound care teams and education to reduce the incidence of pressure ulcers.